(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Comfort has been the goal of working individuals and families. A part of the comfort that people want to experience is dealing with the heat, which is also caused by climate change. Researchers came up with this study to provide air conditioner (AC) services that are now becoming a basic necessity to households, offices, and almost all establishments. Careman Air Conditioning Services offers various services related to an AC machine. These services include survey, installation, cleaning repair, and maintenance. Careman also gives free cleaning, gift cards, and service packages with advertisement through social media and printed media, such as tarpaulin and flyers. The business wants to create a brand of not only providing quality service but also being concerned with its clients. The company’s office is located on the second floor of Celestial Place Building in Barangay Guijo, Francisco Homes, San Jose del Monte, Bulacan. The researchers used descriptive methods design. Half of the respondents in the survey are from Bulacan, and the other half are from Quezon City and Caloocan. The survey had 11 questions that were answered by 90 respondents. The questionnaire gathered information such as the demographic profile of the respondents and preferences of customers in terms of product, price, place, and promotion to assess the acceptability and feasibility of the business to its target market. The company’s strengths and opportunities, as well as how the firm can improve the current position, weaknesses, are extremely helpful in determining where the company is going. The business has a capital of 4 million pesos and is shared by five general partners. Careman Air Conditioning Service’s office has a total floor area of 40 square meters. There is an allotted 6 square meters for the stockroom (lower left) and 4 square meters for the comfort room (upper left). The manager’s office is also 6 square meters. There is a designated table for the marketing and sales supervisor and a receiving area in front of the front desk or reception. The results of the study showed that almost half of the respondents (58%) used AC in their homes and offices. A total of 49% of the respondents use window-type AC. Respondents who want to have AC units cleaned on standard schedule accounted for 86% and those who prefer to have their AC installed by professionals accounted for 88%. Availing AC services from a company at San Jose del Monte was also agreed upon80% of the respondents, 19% answered maybe, while 1% answered no. A total of 90% of the respondents preferred to be reminded for AC unit follow-up service. A total of 91% of the respondents also preferred to have the survey fee deducted from the installation fee, while 9% were not sure. In the preferred medium of contact, phone calls ranked 1st with 54 respondents, 2nd was Facebook messenger with 25 respondents, 3rd was text message with 18, 4th was electronic mail with 12 respondents, and 5th was door to door with 10 respondents. The return of investment is expected to be in 1 year. The researchers came up with a feasible business named Careman Air Conditioning Services. It is located on the second floor of the main road, thereby making it visible and accessible to clients. The business will give more options regarding services offered by the Careman Airconditioning Services. The firm will continue to follow up with customers two times before the scheduled cleaning service. The business will keep promoting the services offered through print media and social media. The firm will also hire more employees as the business grows, and additional incentives will be given to the employees to keep them motivated at work. The income gained by the company should be used productively for the continuous growth of the business.